Optimization of kefir fermentation with plantain peel addition: effects on composition, microbial viability, and sensory quality - Peres, Andrea Pissatto; Puerari, Cláudia; Bento, Juliana Aparecida Correia; Martins, Rafael Alexandre dos Santos; Domingues, Yasmin Ourives; Morzelle, Maressa Caldeira (Frontiers in Nutrition, 2026)
Kefir is a fermented dairy product that can be prepared through microbial fermentation using kefir grains. These grains consist of a symbiotic community of bacteria and yeasts that influence the chemical composition, texture, and sensory characteristics of fermented milk. The incorporation of fruit by-products during fermentation has been explored as a strategy to enhance the functional quality of kefir-based beverages. Among them, plantain (Musa paradisiaca) by-products represent a promising source of bioactive compounds with antioxidant potential and significant amounts of dietary fiber. This study aimed to optimize the fermentation conditions of milk kefir enriched with green plantain peel using response surface methodology and evaluate the microbial viability of the optimized beverage during 21 days of storage. Fermentation parameters were established through preliminary tests, employing UHT milk, sugar (8%), kefir grains, and green plantain peel, fermented for 4 h at 25 °C, using a central composite rotational design (CCRD). The CCRD included two independent variables (X1: green plantain peel 10%−30.0% and X2: Kefir grains, 5%−20%). The optimized formulation, containing 20% green plantain peel and 10% kefir grains, showed increased protein content and reduced carbohydrate levels compared to the control beverage. Although higher inoculum levels did not significantly enhance bioactive compound content, this was likely due to microbial utilization of these metabolites. Lactic acid bacteria (LAB) counts increased over storage, reaching ~104 CFU ml−1 after 21 days, demonstrating the stability of the core kefir microbiota. Sensory evaluation indicated an overall acceptability index of 81.29%. In conclusion, the enrichment of milk kefir with green plantain peel resulted in a nutritionally improved and sensorially accepted beverage, characterized by higher protein density and lower carbohydrate content. These findings highlight the potential of plantain peel as a functional ingredient for the development of enhanced fermented dairy products.